The Role Of Kempek Micro Waqf Bank In Empowering Pesantren-Based Micro Businesses - Najhah Barnamij; Mubarok Fatahillah; Sigit Nurhendi; Sirojudin Akhmad; Ni’amillah Aqiel Siroj (Journal of Islamic Economic Development, 2024)
Bank Wakaf Mikro (BWM), established by OJK and the government, is a strategic step in empowering the economy of communities around Islamic boarding schools. With a group model, simple procedures, and ongoing assistance, BWM plays a role in reducing poverty, providing access to capital without collateral, and countering loan sharking practices. This research, which uses an exploratory qualitative approach, examines community economic empowerment through the implementation of BWM KHAS Kempek. The results show that the BWM CSR grant management mechanism involves: (a) sources of funds from individual and corporate donors, (b) a loan distribution system with intensive mentoring, and (c) locking some of the grant funds in the form of deposits for sustainability. The Akad used includes a grant contract, al-qardh contract, and ju'âlah contract. Pesantren-based micro business empowerment is realized through increasing the number of customers, optimizing business potential, and financial and spiritual assistance through the Weekly Halaqoh (HALMI). This finding confirms the role of pesantren as economic and social drivers of the community. Practically, this research provides insights for policy makers, Islamic financial institutions, and pesantren managers in developing a sustainable and community-based microfinance model. With this approach, it is expected that BWM can further improve the welfare of the community around the pesantren and become an effective model of financial inclusion.